Mengukur Kualitas Layanan Tempat Wisata, Dan Dampaknya Terhadap Kunjungan Ulang - Bagaswara Dei Gratia Lase; Sujana Sujana; Ade Yusdira (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
By this time, the productive age was already overrun by millennials and gen z. Almost every day they do activities so tend to be monotonous and saturated. People always need free time to refresh their brains and themselves from the denseness of daily activities in order to get a new spirit to carry out their activities in the future. Making paratourism is the choice of millennials and gen z today. By doing a paratourism visit, they can refresh their brains and themselves by enjoying tourist facilities and natural scenery in every tourist attraction in Indonesia, especially in Bogor City. Therefore, bogor city tourism service providers must be better at paying attention to the quality of service conditions at tourist attractions in bogor city, in order to be able to create a relationship between tourists and service providers. Good quality of service will give a good impact or feedback that is influencing tourists to make a re-visit in the future. Based on the identification of the above problems, the purpose of this study is to measure Service Quality and impact on Re-Visits based on variables in the ServQual model such as Service Tangible, Service Reliability, Service Responsiveness, Service Assurance, and Service Empathy. The analysis used in this study is SEM (Structural Equation Modelling), in bogor city tourist attractions. Then, the data is obtained through the results of research questionnaires and will be calculated using data processing applications, namely IBM SPSS and LISREL. The results of this study show that The Quality of Service has a significant impact on Re-Visits. With the results of the analysis (1) Service Tangible has a significant and impact on Re-visits with a T-value of 6,29 > a Critical T-value of 1,95, the H0 is rejected which means the Service Tangible has a positive and significant impact on The Re-Visit. (2) The Reliability of the Service shall have a significant and impact on the Re-Visit with a T-value of 5,12 > a Critical T-value of 1,95, the H0 is rejected which means that the Reliability of the Service has a positive and significant impact on the Re-Visit. (3) Service Responsiveness shall have a significant and impact on the Re-Visit with a T-value of 6,73 > a Critical T-value of 1,95, the H0 is rejected which means that the Service Responsiveness has a positive and significant impact on the Re-Visit. (4) Service Assurance has a significant and impact on Re-visit with a T-value of 3,08 > Critical T-value of 1,95, then H0 is rejected which means the Service Assurance has a positive and significant impact on The Re-Visit. (5) Service Empathy has a significant and impact on Re-Visits with a T-value of 9,56 > a Critical T-value of 1,95, the H0 is rejected which means the Service Empathy has a positive and significant impact on Re-Visits. Based on the results of the above analysis, it can be conjured that the Quality of Service has a positive impact and significantly on the Re-visit. The recommendations that can be made to develop the quality of service as an effort to increase the intensity of tourist re-visits is to create a safe, comfortable, clean, and also trendy tourist environment such as adding aesthetic and instagramable photo spots to attract more tourists considering that at this time many tourists are looking for more trendy, contemporary, aesthetic, and instagramable tourist attractions to take selfies to share them on their social media. Service providers can improve the operational standards of employees and service capabilities of each employee by conducting periodic training and developing their services based on feedback provided by tourists through surveys or discussion forms in order to encourage an increase in the number of re-visits from tourists. This research is expected to help tourist service providers in Bogor city in increasing the intensity of re-visits from tourists through the quality of tourist attractions services. Keywords : Measuring Service Quality; Re-visit; Structural Equation Modelling.